Wound bed preparation from a clinical perspective - Halim, A. S. (Medknow Publications & Media Pvt Ltd, 2012)
Wound bed preparation has been performed for over two decades, and the concept is well accepted. The ‘TIME’ acronym, consisting of tissue debridement, infection or inflammation, moisture balance and edge effect, has assisted clinicians systematically in wound assessment and management. While the focus has usually been concentrated around the wound, the evolving concept of wound bed preparation promotes the treatment of the patient as a whole. This article discusses wound bed preparation and its clinical management components along with the principles of advanced wound care management at the present time. Management of tissue necrosis can be tailored according to the wound and local expertise. It ranges from simple to modern techniques like wet to dry dressing, enzymatic, biological and surgical debridement. Restoration of the bacterial balance is also an important element in managing chronic wounds that are critically colonized. Achieving a balance moist wound will hasten healing and correct biochemical imbalance by removing the excessive enzymes and growth factors. This can be achieved will multitude of dressing materials. The negative pressure wound therapy being one of the great breakthroughs. The progress and understanding on scientific basis of the wound bed preparation over the last two decades are discussed further in this article in the clinical perspectives.